Determinants of Bangladesh’s Export Flows to The USA, 2003 – 2010: An Empirical Review - Mohammad A. Ashraf; Abu Zakir Chowdhury (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2010)
IndonesianPenelitian ini menganalisis dampak determinan fungsi ekspor Banglades ke Amerika Serikat selama periode nilai tukar mata uang mengambang bebas, khususnya menguji Hipotesis Linder dalam teori perdagangan internasional tahun 1961. Model tipe gravitasi diestimasi menggunakan data bulanan dari Mei 2003 hingga Mei 2010. Temuan studi ini mendukung Hipotesis Linder. Dari empat variabel, hanya satu variabel yang memiliki koefisien yang sangat nyata. Semua variabel memiliki tanda koefisien yang sama dengan yang dipostulasikan oleh Linder. Temuan studi ini sangat mendukung keabsahan Hipotesis Linder dalam teori perdagangan internasional. EnglishThis study investigates the impacts of the determinants of Bangladesh export functions on the export flows to the USA during the period of free and floating exchange rate regime in Bangladesh in order to review the Linder hypotheses postulated in the international trade theory in 1961. The gravity-type model was estimated using monthly data for the sample period May 2003 – May 2010. The findings of the study support Linder Hypotheses exactly. Among the coefficient estimates of four variables only one variable is found to be statistically highly significant. And the signs of all variable coefficients are exactly the same as postulated by Linder. Thus, the findings of this study are fully in support of the validation of the Linder’s Hypotheses in international trade theory.